Studi Literatur: Pentingnya Perencanaan Personel, Rekrutmen,dan Seleksi Untuk Keberlangsungan Organisasi Bisnis - Nur Dina Kamilia; Riskyta Aqliyatul Amalia; Jasmine Az Zahra Vaesya; Muhammad Chairil Arifin; Mochammad Isa Anshori (Institut Nalanda, 2024)
HR is an important asset of the company. In the current era amid rapid development, people or organizations must be aware of the need for the availability of human resources (HR) with high abilities and competence, HR is one of the factors that cannot be separated from an organization because it is basically a planner, implementer, and also a driving force in achieving organizational goals. The results of research using the literature review method, searching and studying carefully the literature (literature study), show that personnel planning, recruitment, and selection need to be carried out in order to achieve organizational goals effectively and efficiently.